Some properties of the ε∞-product of quotient bornological spaces - B. Aqzzouz; F. Belmahjoub; H. Snoussi (Հայաստանի ԳԱԱ)
Some properties of the ε∞-product defined in (4) are obtained by a study of a kind of isomorphism between the computation of this ε∞-product and the oridnary ε-product of L. Schwartz [9]. The paper contains several corollaries.
Keywords: Mathematics; Science